Malignant hypertension: current challenges, prevention strategies, and future perspectives - Abate Wondesen Tsige; Siraye Genzeb Ayele (Frontiers in Cardiovascular Medicine)
IntroductionBased on office blood pressure (BP) values, hypertension is categorized into three stages: stage 1 (140–159/90–99 mmHg), stage 2 (160–179/100–109 mmHg), and stage 3 (≥180/≥110 mmHg). Malignant hypertension (MHT) is characterized by extreme BP elevation (systolic blood pressure above 200 mmHg and diastolic blood pressure above 130 mmHg) and acute microvascular damage affecting various organs, particularly the retinas, brain, and kidneys.ObjectivesThe pathogenesis, predisposing variables, therapy, and preventive strategies for MHT were examined in this review.Conclusions and recommendationsMalignant hypertension requires prompt and efficient treatment because it is the most severe kind of hypertension that affects target organs. At the same time, there are a number of alternatives available for treating MHT. The International Society of Hypertension 2020 and European Society of Cardiology/European Society of Hypertension 2018 recommendations suggest using labetalol and nicardipine as the first-line choice, with urapidil and nitroprusside serving as alternative medications. Elevated risk of MHT has been linked to many socio-demographic and genetic factors.